Presidential Initiatives as a Tool to Manage U.S. Foreign Assistance Policies in the XXI Century: From George W. Bush Jr. to Joseph R. Biden - V. I. Bartenev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Exploration of bibliography on the U.S. foreign policy reveals a striking and inexplicable lack of scholarly attention to such an interesting phenomenon, as presidential foreign aid initiatives. Such initiatives are studied exclusively in the context of a given administration’ policy but not as an element of the U.S. national system of foreign aid management. This paper is meant to fill this gaping niche. The first section defines a place of such initiatives among the presidential tools to influence foreign aid policies and the reasons behind their proliferation. The second section compares a dozen of the most prominent presidential initiatives of the XXI century — with a special focus on the differences between the most recent Presidential Initiative for Democratic Renewal, launched by Joseph Biden at the Summit for Democracy, and the initiatives of his predecessors. The conclusion is drawn that presidential initiatives have gained in significance over the last two decades due to objective as well as subjective factors. On the one hand, U.S. presidents sought to expand the room for maneuver in foreign aid programming and budgeting, which had been very limited from the very beginning due to the legal constraints and which had contracted even further because of a quick proliferation of Congressional earmarks and directives. On the other hand, one should not underestimate the impact of an unprecedented activism of the George W. Bush that the last three U.S. presidents had to keep in mind in their own aid policies. However, the launch of each initiative was determined by a unique combination of factors operating at the individual, domestic and structural levels. This explains a great variety in circumstances surrounding their launch, documentary and institutional formalization, which did not preclude a number of key similarities: 1) determining the funding volume; 2) providing a long-term perspective; 3) supporting the initiative through authorization acts, presidential orders, memoranda/directives or strategic planning documents issued by the White House; 4) establishing new coordination units. The higher the status of these units and the clearer their mandates were, the more effectively the implementation process went. The launch of the Joseph Biden’s Presidential Initiative for Democratic Renewal — which combines diplomacy and development tools — at the end of his first year in office illustrates the role of the aforementioned factors. His intent to solidify his legacy predetermined the choice of a thematic profile for the first presidential initiative which would reflect his personal ideas and considerations about a pivotal confrontation of the epoch in the most explicit way. However, at least for the time being the Joseph Biden’s initiative stands out in all three main dimensions, which raises doubts about its potential to exert a systemic and long-term influence on the U.S. foreign assistance policies.